PENGARUH TINGKAT SOSIAL EKONOMI ORANG TUA TERHADAP PENDIDIKAN ANAK (Universitas Negeri Semarang, 2023)
This study aims to analyze the effect of parents' socioeconomic level (TSE) on children's education in Baru Village, Muaro Jambi Regency. The population in this study were heads of families (KK) in Baru Village, Muaro Jambi Regency, totaling 166 families. Using the Simple Random Sampling sampling technique, the number of samples was 62 families. The data analysis used is multiple linear regression. The results showed that partially and simultaneously the socio-economic level of parents seen from the level of education and income of parents had an effect on children's education in Baru Village, Muaro Jambi Regency.